Étude de la répartition spatiale du cation Pb dans la végétation forestière au voisinage de l'autoroute 417. - Cardinal, Suzanne. (University of Ottawa (Canada), 1990)
The purpose of this thesis is to explain the spatial diffusion of lead in the forest vegetation along highway 417, around Limoges, Ontario. The analyses of samples taken along both sides of the highway 417 tells us that the wind is the main carrier of particulate lead. Knowing that the predominant winds are from WNW, we conclude that there is a greater concentration of lead north-east of the highway where most of the emanations fall. Lead particles that are carried by the winds settle on the tree foliage and are absorbed in very small quantities by the leaves stomates. The concentration of lead on foliage diminishes gradually with distance from the highway and distilled water will not wash it off. Lead also appears on the tree trunks. There again, the concentration is found to diminish with distance from the highway. The study also reveals that there is no correlation between the concentration of lead on the outside of the tree barks and the inside. Actually, this study cannot explain this phenomenon. (Abstract shortened by UMI.)
Keywords: Agriculture, Forestry and Wildlife.